Online nutrition and T2DM continuing medical education course launched on state-level medical association - Hicks KK; Murano PS (Advances in Medical Education and Practice, 2017)
Kristen K Hicks, Peter S Murano Texas A&M University, Department of Nutrition and Food Science, College Station, TX, USA Objective: The purpose of this research study was to determine whether a 1-hour online continuing medical education (CME) course focused on nutrition for type 2 diabetes would result in a gain in nutrition knowledge by practicing physicians.  Methods: A practicing physician and dietitian collaborated to develop an online CME course (both webinar and self-study versions) on type 2 diabetes. This 1-hour accredited course was launched through the state-level medical association’s education library, available to all physicians. Results: Physicians (n=43) registered for the course, and of those, 31 completed the course in its entirety. A gain in knowledge was found when comparing pre- versus post-test scores related to the online nutrition CME (P<0.0001). Conclusions: Online CME courses launched via state-level medical associations offer convenient continuing education to assist practicing physicians in addressing patient nutrition and lifestyle concerns related to chronic disease. The present diabetes CME one-credit course allowed physicians to develop basic nutrition care concepts on this topic to assist patients in a better way. Keywords: continuing medical education, CME, online/computer-based education, nutrition education, preventive nutrition and chronic disease, type 2 diabetes